The Evaluation of Portfolio Performance: The Risk-Adjusted Performance of Sharia Equity Mutual Funds using Sharpe, Treynor, And Jensen’s Alpha based on Daily Data on period 2022 - 2025 - Hardiyanti, Siti Epa (Management Science Research Journal, 2025)
This study evaluates the risk-adjusted performance of three Sharia equity mutual funds in Indonesia (Manulife Syariah Sektoral Amanah, Mandiri Investa Ekuitas Syariah, and Batavia Dana Saham Syariah) using daily data from 2022 to 2025. The analysis employs daily returns, excess returns, total volatility, market beta, and three major performance measures: the Sharpe Ratio, Treynor Ratio, and Jensen’s Alpha. Results show that all three funds consistently underperformed the Jakarta Islamic Index (JII), reflected in negative Sharpe and Treynor Ratios and negative, statistically insignificant Jensen’s Alpha values. These findings indicate that performance is predominantly driven by market movements rather than managerial skill. The study contributes empirical evidence on the behavior of Islamic mutual funds in volatile market periods and offers practical insights for investors seeking risk-adjusted performance evaluation in Islamic finance contexts.